Adsorption kinetics and equilibrium of cooper and zinc on sponge gourd fibre - Ng, Suk Ying (2008)
The kinetics and equilibrium of Cu and Zn adsorption by sponge gourd fibre were investigated according to batch method. The final concentration of Cu and Zn in solution was determined using atomic adsorption spectrophotometer. The experimental results showed that the adsorption of both metals was rapid during the first 10 minutes and thereafter slowed down until equilibrium was attained after 60 minutes. The adsorption can be well described ( R²~1.0000) by pseudo-second order kinetic model. The adsorbed amount of Cu and Zn increased while the percentage decreased with increase in initial metal concentration. The adsorption conforms (R2 >0.96) to both Freundlich and Langmuir isotherms. The maximum adsorption capacity, qmax, of sponge gourd fibre for Cu and Zn was 5000.0 μgg⁻¹ and 2000.0 ggg⁻¹, respectively. At fixed initial concentration, percentage removal of the metals showed an increasing trend with increase in adsorbent dosage.